Characterization of ANITA and QMN neutron beams at TSL using proton recoil techniques - Naitou Y. (2017)
Neutron beam characterization measurements have been carried out in both the ANITA and QMN modes using the incident proton beam of 180 MeV at the The Svedverg Laboratory (TSL) in Uppsala. Th e spectral neutron flux data have been obtained by measuring elastic np-scattering with the Medley setup. The experimental results in the ANITA and QMN modes are compared with an MCNPX simulation and with the systematics of QMN spectra, respectively.